H83PDC – Process

Dynamic & Control
Lecture 3 –
Transfer Function,
Laplace Transforms & Linearisation

Lecture Outline
Transfer Function 
Laplace Transforms 
Multi-variable Linearisation 

H83PDC Process Dynamic & Control

Lecture 3 - 2

Applicable to
linear dynamic
behaviour only

Alternative
dynamic
model to
ordinary
differential
equations
(ODE)

Based on
Laplace
transforms

Transfer
Function
Models
To determine
the dynamics
behaviour of a
process after
changes in
input variables

Characterises
the dynamic
relationship of
two process
variables: input
(cause) & output
(effect)

H83PDC Process Dynamic & Control

Important in
design &
analysis of
control system

Lecture 3 - 3

Laplace Transforms
To inverting solutions
from the s-domain to
the t-domain

H83PDC Process Dynamic & Control

Lecture 3 - 4

The Laplace transform of a function f(t) is defined as:   = L () =  () .

the transform becomes a function of the Laplace transform variable. s  Inverse Laplace transform (L-1) operates on the function F(s) and converts it to f(t) () = L    H83PDC Process Dynamic & Control Lecture 3 . s is a complex independent variable f(t) = a function of time to be transformed L = an operator. defined by the integral  Function f(t) must satisfy mild conditions that include being piecewise continuous for 0 < t < ∞  When the integration is performed. dt F(s) = symbol for the Laplace transform.5 .

Properties of Laplace Transform  It is linear operator  Apply the superposition principle: L   + () =() + Y(s)  Multiplicative constants can be factored out of the operator H83PDC Process Dynamic & Control Lecture 3 .6 .

Laplace Transforms for Simple Functions A. L  =   . Constant Function For f(t) = a (a constant).

   .

∞ =−   0  =0− −   =  H83PDC Process Dynamic & Control Lecture 3 .7 .

Step Function The unit step function is defined as. 0  < 0   = 1  ≥ 0 1 L () =  1 0 H83PDC Process Dynamic & Control t Lecture 3 .8 .B.

Derivatives  First Derivative   .C.

L =     Integrating by parts.  ∞ .

.

9 . L =  ()  +     0  = L () −  0 =   − (0) H83PDC Process Dynamic & Control Lecture 3 .

10 . Second Derivatives !  φ L =L !   = φ  − φ 0 =    − (0) − φ 0 =  !   −  0 −  " (0)  n-th Order Derivatives #  #   −  #   0 −  # !  L =   # − # ! 0 −  #  (0) H83PDC Process Dynamic & Control Where φ= "   =  φ  =   − (0)  0 − ⋯⋯ Lecture 3 .

Exponential Functions Where  > 0 L %.D.

=  %.

.

  =  (%& ).

  1 = − + 1 = + %& .

∞  0 H83PDC Process Dynamic & Control Lecture 3 .11 .

Trigonometric Functions 1 1 -.E.

L cos + = L + L -.

2 2 1 1 1 + = 2  − /+  + /+ Where -.

+ -.

12 . cos + = 2 / ≜ −1 1  + /+ +  − /+ = 2 ! − +!  = !  + +! H83PDC Process Dynamic & Control Lecture 3 .

F. Rectangular Pulse Function <0 0   = 1ℎ 0 ≤  ≤ 4  ≥ 4 0   =    .

  .

5 =  ℎ .

  ℎ .

4 =− 6  0 ℎ = 1 − .

5  H83PDC Process Dynamic & Control Lecture 3 .13 .

L 7() = lim 1 . Impulse Function 7  = 0 for  ≠ 0  7   = 1 .G.

5 → 4  ℎ=  .

5 1 − .

5  .

5 7  = lim =1 .

14 . ∴ L 7() =  H83PDC Process Dynamic & Control Unit IMPULSE Area=1 0 t Unit PULSE Area=1 0 t Lecture 3 .5 →  If the impulse magnitude (area twh) is a constant a rather than unity.

H. Ramp Function L  =   ∙ .

 =    ∙ .

   Where ∞   ∙ .

 = ?@  −  @ ? ?= 0  .

  @ = −  .

∞ 1 .

= − −  − ?  0   1 1 .

∞ =0− − −   0 1 = !   ∴  = !  ? =  @ = .

Slope = a 0 t 0  < 0   =   ≥ 0 H83PDC Process Dynamic & Control Lecture 3 .15 .

Example 1 Solve the differential equation using Laplace transforms: 5 Solution dy + 4y = 2 dt where y (0) = 1  dy  L  5 + 4 y  = L ( 2)  dt   dy  L 5  + L (4 y ) = L (2)  dt   dy  5L  = 5(sY (s ) − 1) = 5sY (s ) − 5  dt  4L ( y ) = 4Y (s ) 2 L (2) = s H83PDC Process Dynamic & Control Lecture 3 .16 .

5 + 0.4  = L−1   ( ) s s + 0 . 8   y (t ) = 0.5e −0.Substitute the individual terms: 5sY (s ) − 5 + 4Y (s ) = 2 s 2 Y (s )(5s + 4 ) = + 5 s 5s + 2 Y (s ) = s(5s + 4 )  5s + 2  L [Y (s )] = L   ( ) s 5 s 4 +   −1 −1  s + 0 .8t H83PDC Process Dynamic & Control Lecture 3 .17 .

18 . s+5 Y (s ) = 2 s + 5s + 4 s+5 α1 α2 = + (s + 1)(s + 4) (s + 1) (s + 4) Where α1 and α2 are unspecified coefficients  Multiply both sides by (s+1)(s+4) s + 5 = α1 ( s + 4) + α 2 ( s + 1) = (α1 + α 2 ) s + (4α1 + α 2 )  Equating coefficients of each power of s: 1 = α1 + α 2 − − − − − − − (1) 5 = 4α1 + α 2 − − − − − −(2) 4 1 α1 = . α 2 = − 3 3 H83PDC Process Dynamic & Control Lecture 3 .Laplace Transform: Partial Fraction Expansion   High-order denominator polynomial in a Laplace transform can be factored into a product of first-order terms Then the transform can be expanded into the sum of two partial fractions E.g.

19 .Example 2 Solve the differential equation using Laplace transforms: dy d3y d2y + 6 + 11 + 6y =1 3 2 dt dt dt where y( 0 ) = y' ( 0 ) = y' ' ( 0 ) = 0 Solution  d3y  3 L 3  = s Y ( s )  dt   d2y  L 6 2  = 6 s 2Y ( s )  dt   dy  L11  = 11sY ( s )  dt  L (6 y ) = 6Y ( s) 1 L (1) = s H83PDC Process Dynamic & Control Lecture 3 .

α 3 = − . 6 2 2 H83PDC Process Dynamic & Control α4 s+3 1 α4 = − 6 Lecture 3 .20 .Rearranging and factoring Y(s): 1 Y ( s )( s + 6 s + 11s + 6) = s 3 2 1 Y (s) = s ( s 3 + 6s 2 + 11s + 6) Factor the denominator into a product of first-order terms: s ( s 3 + 6s 2 + 11s + 6) = s ( s + 1)( s + 2)( s + 3) The partial fraction expansion: 1 Y ( s) = s ( s + 1)( s + 2)( s + 3) = α1 s + α2 + α3 s +1 s + 2 + Solve for the unspecified coefficients: 1 1 1 α1 = . α 2 = − .

21 .Change to time-domain by inverting each term individually: y (t ) = L−1[Y ( s )]  1/ 6 1/ 2 1/ 2 1/ 6  =L  − + +  s +1 s + 2 s + 3   s 1 −1  1  1 −1  1  1 −1  1  1 −1  1  = L  − L  + L  − L   6 s 2  s +1 2  s+2 6  s +3 −1 1 1 − t 1 − 2 t 1 − 3t y (t ) = − e + e − e 6 2 2 6 H83PDC Process Dynamic & Control Lecture 3 .

22 .General Procedure for Solving Differential Equations Time-domain ODE Initial conditions Laplace-domain Step 1 Take Laplace transform Step 2 Solve for N(s) Y(s) = D(s) Step 3 Factor D(s) & perform partial fraction expansion Solution y(t) Step 4 Take inverse Laplace transform H83PDC Process Dynamic & Control Lecture 3 .

Laplace Transform: Limit Theorems  Final Value Theorem:  Allows determination of final steady state perturbation in y(t) lim y (t ) = lim sY ( s ) t →∞  s →0 Initial Value Theorem:  Allows determination of the initial condition in y(t) (often zero perturbation) lim y (t ) = lim sY ( s ) t →0 s →∞ H83PDC Process Dynamic & Control Lecture 3 .23 .

Example 3 5s + 2 Y (s) = s (5s + 4) Initial value: 5s + 2 =1 s →∞ 5s + 4 y (0) = lim[ sY ( s )] = lim s →∞ Final value: 5s + 2 y (∞) = lim[ sY ( s )] = lim = 0 .24 .5 s →0 s →0 5s + 4 H83PDC Process Dynamic & Control Lecture 3 .

h-1.Transfer Function f(t) Process y(t) Single input and output process F(s) KG(s) Y(s) Block diagram Y(s) = KG(s) × F(s) F(s) = transform of movement in the FORCING variable Y(s) = transform of movement in the RESPONSE variable KG(s) = the TRANSFER FUNCTION K = the steady state gain factor (units of Y/F) G(s) = the dimensionless transfer function (where s has units of time-1.25 . s-1) H83PDC Process Dynamic & Control Lecture 3 . min-1.

Development of Transfer Functions Example: Stirred-Tank Heating Process (Constant Holdup) Stirred-tank heating process with constant holdup. The density and heat capacity C of the liquid are assumed to be constant. Heat losses are negligible.26 . 2. 3. Liquid holdup V is constant because the inlet & outlet flow rates are equal. V Assumptions: 1. H83PDC Process Dynamic & Control Lecture 3 . ∴ Their temperature dependence is neglected. 4. Perfect mixing ∴ The exit T is also the temperature of the tank contents.

Assuming constant liquid holdup and flow rates: dT V ρC = wC (Ti − T ) + Q (2-36) dt Suppose the process is at steady state: 0 = wC (Ti − T ) + Q Subtract (2) from (2-36): dT V ρC = wC (Ti − Ti ) − (T − T )  + ( Q − Q ) dt (2) (3) Simplify: dT ′ V ρC (4) = wC (Ti′ − T ′ ) + Q′ dt where the “deviation variables” are T ′ = T − T . Q′ = Q − Q H83PDC Process Dynamic & Control Lecture 3 . Ti′ = Ti − Ti .27 .

Q′ & Ti′ G1 (process) has gain K and time constant τ G2 (disturbance) has gain=1 and time constant τ K = process gain H83PDC Process Dynamic & Control Lecture 3 .Take L of (4): ABC D "  − D " 0 = EC DF "  − D "  + G "  (5) At the initial steady state. T′(0) = 0 Rearrange (5) to solve for:  K  ′  1  ′ T ′( s ) =  Q s +  ( )   Ti ( s )  τ s +1  τ s +1  where K = 1 and τ = V ρ wC w In general form:       (6) T ′(s)=G1(s)Q ′(s) + G 2(s)Ti′(s) System can be forced by a change in either Ti or Q Both are first-order processes G1 and G2 are transfer functions and independent of the inputs.28 .

29 . Ti′= 0 then Ti′(s) = 0. Therefore. D′() = J () G′()  If there is no change in heater input. The effects of changes in both Q and Ti are additive because the Principle of Superposition is valid  The transfer function can determine the output response to any change in an input  If there is no change in inlet temperature. Therefore. D′() = J! () DF ′() H83PDC Process Dynamic & Control Lecture 3 . Q′= 0 then Q′s = 0.

Solution The energy balance for the nominal conditions: EC DK − DLF = GK ∴ DK = 100℉ For inputs changes: DF" 90 − 70 20 1600 − 1920 320 "  = = and G  = =−     H83PDC Process Dynamic & Control Lecture 3 .32 Btu/lb°F. V = 1.60 ft3 Calculate the output temperature response. C = 0.30 . ρ = 62.4 lb/ft3.Example: Stirred-Tank Heating Process (Constant Holdup) When the stirred-tank heating process operates at steady state: Ti = 70°F. w = 200 lb/min. Q = 1920 Btu/min. if the inlet temperature is changed to 90°F and the heater input is changed to 1600 Btu/min.

5 + 1  0.5 + 1) (0.4) = 0.5 + 1) (0.5 min 200 1 ℉ Process gain.1 Vρ K= and τ = wC w (1.5 + 1) The corresponding time-domain solution is: D  = DK + D "  D  = 100 + 15(1 − !.32) Time constant. X = = 1.0156 320 1 20 D  = − + 0. U =  K  ′  1  ′ T ′( s) =  Q s +  ( )   Ti ( s )  τ s +1   τ s +1  (6) 0.6)(62.56 × 10 ! Btu/min (200)(0.5 + 1  " D" −5 20 15  = + = (0.

31 . ) H83PDC Process Dynamic & Control Lecture 3 .

32 .Properties of Transfer Function Models  Steady-State Gain The steady-state of a TF can be used to calculate the steady-state change in an output due to a steady-state change in the input K=  y2 − y1 u2 − u1 (4-38) Order of a TF Model The order of the TF is defined to be the order of the denominator polynomial or equal to the order of the ODE H83PDC Process Dynamic & Control Lecture 3 .

which is the input to G2 ^a _ = `a _ b _ ^c _ = `c _ ^a _ = `c (_)`a (_)b _ H83PDC Process Dynamic & Control Lecture 3 . Additive Property A single process output variable (Y) can be influenced by more than one input (U1 and U2) acting individually or together ^ _ = `a _ ba _ + `c (_)bc (_)  Multiplicative Property Two processes with transfer functions G1 and G2 are in a series configuration and the input U(s) to G1 produces an output Y1(s).33 .

u ∂f ∂u (u − u ) y . exponential dependence of reaction rate on temperature  A linear approximation of a nonlinear steady-state model is most accurate near the point of linearisation  For a nonlinear dynamic model: dy = f ( y. the reference point for linearisation is the nominal steady-state operating point (K. u ) ≅ f ( y. ?K)  f ( y. u ) dt By using a Taylor series expansion. u ) +  ∂f ∂y ( y − y) + y .g.u The linearised differential equation in terms of y’ and u’: dy′ ∂f ∂f ′ = y + u′ dt ∂y s ∂u s H83PDC Process Dynamic & Control Lecture 3 .Linearisation of Nonlinear Models  Dynamic behaviour could depend on the process variables in a nonlinear manner.34 . e.

stream 2 is pure solute (x2 = 1). However.Example: Stirred-Tank (Constant Holdup) Assume the liquid volume (V) is constant but inlet composition x1 and inlet flow rates w1 and w2 can vary.35 . Mass & component balances: dV ρ = w1 + w2 − w dt dx ρV = w1 ( x1 − x ) + w2 ( x 2 − x ) dt H83PDC Process Dynamic & Control Lecture 3 .

36 .Nonlinearities appear in equation due to the product terms w1x1 etc. Step 1 Find the steady-state values of x and w by setting the derivatives equal to zero and substituting the steady-state values: 0=E L + E L! − E L 0=E L (̅ − ̅ ) + E L ! (̅! − ̅ ) Step 2 Linearise about the nominal steady-state values:  ′ BA = BA   f f f =  − ̅ + ( − ̅ ) + (E − E L ) f f fE f + (E! − E L!) fE! H83PDC Process Dynamic & Control Lecture 3 .

The partial derivatives: f = −E L − E L! f f =E L f f = ̅ − ̅ fE f = 1 − ̅ fE! Step 3 Substitute the partial derivatives and introduce deviation variables: ′ BA = −E L " + E L  " + ̅ − ̅ E " + (1 − ̅ )E! "  H83PDC Process Dynamic & Control Lecture 3 .37 .

x’(0) = 0: BA "  = −E L "  + E L  "  + ̅ − ̅ g "  + 1 − ̅ g! "  Rearranging and dividing by E L: BA E L " ̅ − ̅ " 1 − ̅ " +1   =   + g  + g! "  E E L L E L E L Define: BA U= E L E L 1 − ̅ ̅ − ̅ X = .Step 4 Take Laplace transform of both sides of equation with the initial condition. X! = . Xi = E L E L E L H83PDC Process Dynamic & Control Lecture 3 .38 .

three input-output transfer functions can be derived: "   X " J  = " = U + 1   J! " "  X!  = = " U + 1 g!  " "  Xi  = = " U + 1 g  Ji H83PDC Process Dynamic & Control Lecture 3 .39 .Step 5 Gives the relationship for the single output and three inputs: " X X! Xi " "  =   + g!  + g "  U + 1 U + 1 U + 1 Also.

40 .General Procedure for Developing TF Models H83PDC Process Dynamic & Control Lecture 3 .